β-Arrestin interacts with the beta/gamma subunits of trimeric G-proteins and dishevelled in the Wnt/Ca(2+) pathway in xenopus gastrulation - Seitz, Katharina; Dürsch, Verena; Harnoš, Jakub; Bryja, Vitezslav; Gentzel, Marc; Schambony, Alexandra (PloS one, 2014)
β-Catenin independent, non-canonical Wnt signaling pathways play a major role in the regulation of morphogenetic movements in vertebrates. The term non-canonical Wnt signaling comprises multiple, intracellularly divergent, Wnt-activated and β-Catenin independent signaling cascades including the Wnt/Planar Cell Polarity and the Wnt/Ca(2+) cascades. Wnt/Planar Cell Polarity and Wnt/Ca(2+) pathways share common effector proteins, including the Wnt ligand, Frizzled receptors and Dishevelled, with each other and with additional branches of Wnt signaling. Along with the aforementioned proteins, β-Arrestin has been identified as an essential effector protein in the Wnt/β-Catenin and the Wnt/Planar Cell Polarity pathway. Our results demonstrate that β-Arrestin is required in the Wnt/Ca(2+) signaling cascade upstream of Protein Kinase C (PKC) and Ca(2+)/Calmodulin-dependent Protein Kinase II (CamKII). We have further characterized the role of β-Arrestin in this branch of non-canonical Wnt signaling by knock-down and rescue experiments in Xenopus embryo explants and analyzed protein-protein interactions in 293T cells. Functional interaction of β-Arrestin, the β subunit of trimeric G-proteins and Dishevelled is required to induce PKC activation and membrane translocation. In Xenopus gastrulation, β-Arrestin function in Wnt/Ca(2+) signaling is essential for convergent extension movements. We further show that β-Arrestin physically interacts with the β subunit of trimeric G-proteins and Dishevelled, and that the interaction between β-Arrestin and Dishevelled is promoted by the beta/gamma subunits of trimeric G-proteins, indicating the formation of a multiprotein signaling complex.
Keywords: vápníková signalizace; aktivace enzymů; Animals; arrestiny; fosfoproteiny; protein dishevelled; Adaptor Proteins, Signal Transducing; Enzyme Activation; gastrulace; Dishevelled Proteins; proteinkinasa C-alfa; embryo nesavčí; adaptorové proteiny signální transdukční; podjednotky proteinů; Protein Kinase C-alpha; vazba proteinů; Protein Transport; Phosphoproteins; beta arrestiny; Wnt Signaling Pathway; transport proteinů; Gastrulation; Xenopus laevis; Arrestins; signální dráha Wnt; Calcium Signaling; Protein Subunits; Embryo, Nonmammalian; zvířata; heterotrimerní G-proteiny; Protein Binding; beta-Arrestins; Heterotrimeric GTP-Binding Proteins